Free Vibration Analysis for Dynamic Stiffness Degradation of Cracked Cantilever Plate - Dawood, Hussain A.; Abdullah, Oday. I. (Al-Khwarizmi Engineering Journal, 2017)
In the present work a dynamic analysis technique have been developed to investigate and characterize the quantity of elastic module degradation of cracked cantilever plates due to presence of a defect such as surface of internal crack under free vibration. A new generalized technique represents the first step in developing a health monitoring system, the effects of such defects on the modal frequencies has been the main key quantifying the elasticity modulii due to presence any type of un-visible defect. In this paper the finite element method has been used to determine the free vibration characteristics for cracked cantilever plate (internal flaws), this present work achieved by different position of crack. Stiffness reduction in term of elastic material properties is analyzed through a parametric study of crack density factor. Results are given for Young’s modulus and shear modulus variation with respects the vibrational characteristics.